PEMANFAATAN KOMPOS BLOK LIMBAH KULIT KOPI SEBAGAI MEDIA TANAM - Elida Novita; Anis Fathurrohman; Hendra Andiananta Pradana (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2018)
Coffee pulp and coffee husk has nutrients content that can be utilized for plant growth. One of their utilization is as growing media called compost block. The purposes of this study were to know the macro nutrients content in the coffee solid waste compost and the influence of compost block utilization to the crop growth rate of cayenne pepper. The experimental design was a Completely Randomized Design (CRD) with four treatments and three replications. The treatments were soil as control (K), coffee pulp compost block (KOB), coffee husk compost block (KOK), and mixed compost block (KOC). The parameters measured in this study were plant height, number of leaves, leaf area, and the diameter of stem. Data analysis used Standard Error of Mean and presented in error bar. The results showed that mixed compost has the highest macro nutrients content. The content of macro nutrients in coffee pulp compost were 1,86% of Nitrogen (N), 0,16% of Phospor (P), and 1,39% of Potassium (K); coffee husk compost were 1,68% of N, 0,11% of P, and 1,70% of K; and also mixed compost were 3,22% of N, 1,09% of P, and 1,39% of K. The mixed compost block treatment gives the best result to vegetative growth rate of cayenne pepper. The growth rate of plant height was 7,88 cm/week; number of leaves was 2 leaves/week; leaf area was 7,20 cm2/week; and the diameter of stem was 0,03 cm/week.